A preliminary transcriptomic approach to elucidate post harvest ripening of plum fruit - Bonghi, Claudio; Ramina, Angelo; Manganaris, George A. (My University, 2010)
The aim of the present study was to dissect common and/or diverse mechanisms regulating plum (Prunus salicina) fruit ripening in genotypes characterized by different patterns of ethylene production. Fruit of an ethylenesuppressed cultivar ('Shiro') and a cultivar characterized by the typical increase of ethylene production during fruit ripening ('Santa Rosa') were harvested at commercial maturity stage and allowed to further ripen at room temperature (23°C) up to 4 days. While non-detectable amounts of ethylene were recorded in 'Shiro' fruit, a typical climacteric behavior was observed in 'Santa Rosa' plums. For comparative purposes, the peach microarray μPEACH 1.0 containing 4,806 oligonucleotides corresponding to an equal number of genes expressed in peach fruit was employed for transcript profiling during postharvest ripening of both cultivars. Intriguingly, transcript levels of genes involved in ethylene biosynthesis, primarily 1-aminocyclopropane-1-carboxylate synthase, appeared to increase during the progress of 'Shiro' fruit ripening, following the same pattern as in 'Santa Rosa' plums. These data suggest that an induction of the ethylene biosynthetic pathway is present also in plum cultivars in which the burst of ethylene is not detectable. Expression levels of other genes implicated in auxin metabolism, antioxidant system and stress response followed the same pattern in both cultivars. Overall, this preliminary transcriptomic approach tried to elucidate the flow of events that accompany postharvest ripening of plum cultivars with diverse properties in relation to ethylene evolution
Keywords: Climacteric; DNA microarrays; Peach; Plum; Rosaceae; Prunus; Fruit--Ripening